The Relationship Between Changes in Dynamic Risk Factors and the Predictive Validity of Risk Assessments Among Youth Offenders - Clarke, Maggie C. (Criminal justice and behavior, 2017)
The Youth Level of Service/Case Management Inventory (YLS/CMI) is a widely used risk assessment tool for youth offenders. It is intended to be administered regularly to capture changes in criminogenic needs and thus inform case management during a youth’s sentence. However, there is a dearth of research examining whether updated assessments are more predictive of recidivism than initial assessments. We examined whether including dynamic risk factors increased the predictive validity of the YLS/CMI and whether changes in dynamic risk scores improved the prediction of recidivism. Two hundred youth offenders were tracked from their first risk assessment conducted at probation to their most recent risk assessment completed prior to first reoffense or study end date. Inclusion of dynamic risk scores improved predictive accuracy above static risk and updated dynamic risk scores improved accuracy over those obtained from the initial assessment, supporting the utility of the YLS/CMI as a reassessment tool.